Complex formation between NheB and NheC is necessary to induce cytotoxic activity by the three-component Bacillus cereus Nhe enterotoxin. - Uta Heilkenbrinker (Public Library of Science (PLoS), 2013)
The nonhemolytic enterotoxin (Nhe) is known as a major pathogenicity factor for the diarrheal type of food poisoning caused by Bacillus cereus. The Nhe complex consists of NheA, NheB and NheC, all of them required to reach maximum cytotoxicity following a specific binding order on cell membranes. Here we show that complexes, formed between NheB and NheC under natural conditions before targeting the host cells, are essential for toxicity in Vero cells. To enable detection of NheC and its interaction with NheB, monoclonal antibodies against NheC were established and characterized. The antibodies allowed detection of recombinant NheC in a sandwich immunoassay at levels below 10 ng ml⁻¹, but no or only minor amounts of NheC were detectable in natural culture supernatants of B. cereus strains. When NheB- and NheC-specific monoclonal antibodies were combined in a sandwich immunoassay, complexes between NheB and NheC could be demonstrated. The level of these complexes was directly correlated with the relative concentrations of NheB and NheC. Toxicity, however, showed a bell-shaped dose-response curve with a plateau at ratios of NheB and NheC between 50:1 and 5:1. Both lower and higher ratios between NheB and NheC strongly reduced cytotoxicity. When the ratio approached an equimolar ratio, complex formation reached its maximum resulting in decreased binding of NheB to Vero cells. These data indicate that a defined level of NheB-NheC complexes as well as a sufficient amount of free NheB is necessary for efficient cell binding and toxicity. Altogether, the results of this study provide evidence that the interaction of NheB and NheC is a balanced process, necessary to induce, but also able to limit the toxic action of Nhe.